Pelatihan Pemanfaatan Limbah Pertanian dan Limbah Kotoran Ternak menjadi Produk Pupuk Organik Padat di Kelurahan Bontonompo - Wati, Mega; Maulana, Muh; Mustarin, Amirah; Firdauziyah, Samiyah (Departemen Teknologi Pertanian Universitas Hasanuddin, 2024)
Bontonompo village is a center where there are cattle farmers in its area. The maintenance of livestock in Bontonompo village in general is still sober and has not yet carried out waste treatment in the form of solid manure. In addition, bontonompo village is also an area that has a farmer's livelihood where these farmers grow rice. Mayarakat in general does not know the processing technology and benefits if they manage agricultural waste and manage livestock waste properly. This has the potential to cause environmental pollution, air pollution and can cause disturbances in agricultural products and health both in humans and livestock themselves. In fact, agricultural waste and solid cow dung waste can be processed and used into solid organic fertilizer. The purpose of this activity is to provide knowledge and skills to the community in order to be able to process agricultural waste and manure waste into solid organic fertilizers and natural pesticides that are environmentally friendly. The methods used in this activity start from socialization, material provision, training, evaluation and mentoring. As a result of this activity, the community knows and is skilled in processing agricultural waste and manure waste into solid organic fertilizer and natural pesticides. The community also has the mindset to process and utilize waste and existing local potential to be used as useful and economicallyvaluableproducts.Keywords: Agricultural waste, livestock waste, organic fertilizers.